Current Situation and Development Directions of Railway Transport in Thailand and the ASEAN Region - Pholkhank, Banjong; Khojuantheo, Saroj; Pabu, Janya; Lertlam, Kosol; Thisong, Phumiphat; Tangcharoenworakul, Waranya; Phonkho, Ardnarong; Ngernbutkotru, Kitphorn (Research and Development Journal Sisaket Rajabhat University, 2026)
This research, titled “Current Status and Development Guidelines for Rail Transport in Thailand and the ASEAN Region,” aims to examine the current state of rail infrastructure, analyze logistics connectivity, and formulate strategic recommendations for Thailand’s transition into an ASEAN rail hub. The study employs a mixed-methods approach, utilizing statistical secondary data analysis and in-depth interviews with industry experts to assess the nation’s competitiveness across multiple dimensions. In the first phase, the assessment of the current status reveals that Thailand’s double-track rail network has expanded to cover over 3,150 kilometers of strategic routes. This expansion has increased line capacity from 54 trains per day to 150-200 trains per day and reduced waiting times for train crossings by an average of 30-50%. However, the modal share of rail freight remains at approximately 7-9%, which is below the National Strategic Goal of 15%, primarily due to constraints in seamless connectivity at major freight terminals. The second phase, focusing on ASEAN connectivity, finds that the North-South Economic Corridor (NSEC)—particularly the Thailand-Laos-China route—has seen an average annual increase of 25% in freight volume through the Nong Khai border since 2022. The analysis indicates that standardizing signaling systems to ETCS Level 1 could increase the average speed of cross-border freight trains from 40 km/h to 70-80 km/h, potentially reducing cross-border logistics costs by 15-20% compared to road transport. In the third phase, the research proposes a roadmap to elevate Thailand as a regional hub through the development of Dry Ports in four strategic provinces: Chachoengsao (supporting the EEC), Khon Kaen (linking Laos-China), Nakhon Ratchasima (the Gateway to the Northeast), and Nakhon Sawan (the Northern Hub). These developments are projected to reduce logistics costs relative to GDP to 10-11% by 2027. Additionally, the study recommends establishing a Railway Technology Research and Development Institute to produce 2,500 specialized personnel annually to meet the labor demands of the ASEAN rail market. The findings suggest that integrating these four dry ports with the double-track network will be a critical mechanism in driving Thailand toward becoming the region’s most vital and sustainable strategic transportation intersection.